Iron-nitrogen composite porous carbon microsphere material as well as preparation method and application thereof

Through the design of iron-nitrogen composite porous carbon microsphere materials, the combination of Fe0, Fe3N, FeCx, and Fe3O4 is used to solve the fluidity and activity problems of zero-valent iron in groundwater repair, and improve the removal efficiency of chlorinated hydrocarbon pollutants , achieving more efficient groundwater repair effect.

CN119236993APending Publication Date: 2025-01-03SHANDONG JIUSI ENVIRONMENTAL PROTECTION ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411360121.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In groundwater repair, zero-valent iron accumulates into large particles due to magnetic properties and high surface energy, loses fluidity, has short activity life, high cost, and poor binding of surface hydrophilicity and hydrophobic pollutants, which reduces the removal efficiency.

Method used

Iron-nitrogen composite porous carbon microspheres are used to form a porous carbon matrix through hydrothermal reaction, and the carbon matrix with porous structure is loaded with Fe0, Fe3N, FeCx, Fe3O4, Fe0 as electron donors, and Fe3N, FeCx, and Fe3O4 as reduction active sites, which improves the material stability and degradation efficiency.

Benefits of technology

It extends the active life of zero-valent iron and improves the removal efficiency of chlorinated hydrocarbon pollutants. The zero-valent iron inside the material is not easy to oxidize, enhances the affinity for hydrophobic pollutants, and slowly releases degradation products, suitable for groundwater In-situ repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236993A_ABST
    Figure CN119236993A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts for groundwater remediation, in particular to an iron-nitrogen composite porous carbon microsphere material and a preparation method and application thereof. The invention provides an iron-nitrogen composite porous carbon microsphere material, which comprises a porous carbon matrix, and Fe < 0 >, Fe < 3 > N, Fe < C > x and Fe < 3 > O < 4 > loaded on the porous carbon matrix, the Fe < 0 > is an active electron donor, and the Fe < 3 > N, the Fe < C > x and the Fe < 3 > O < 4 > are reduction active sites; wherein based on the mass of the iron-nitrogen composite porous carbon microsphere material, the content of Fe < 0 > is 25-33 wt%. According to the material, carbon serves as a matrix, Fe0, Fe3N, FeCx and Fe3O4 serve as composite components, the surface is porous, internal zero-valent iron and the like are not prone to oxidation, and the problem that existing pure zero-valent iron microspheres are rapidly passivated in the repairing process can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts for groundwater remediation, and in particular to an iron-nitrogen composite porous carbon microsphere material and a preparation method and application thereof. Background Art

[0002] Over the years, zero-valent iron (Fe 0 )-based groundwater in-situ remediation technology has received extensive attention and in-depth research at home and abroad. 2+ +2e - →Fe(s),E 0 =-0.44V), and its abundant source and low price make it widely used in the field of environmental remediation to remove and degrade organic or inorganic pollutants. However, as an important material in groundwater in-situ remediation technology, zero-valent iron faces some technical challenges and limitations.

[0003] First, due to its magnetism and high surface energy, nano-zero-valent iron easily aggregates into large particles, which will lead to the loss of underground fluidity, thus affecting its distribution and effect in contaminated sites. Secondly, zero-valent iron is highly active but has a short lifespan, which means that it cannot continuously degrade pollutants and needs to be replaced or replenished regularly, increasing the cost of operation and maintenance. Furthermore, the surface of zero-valent iron is hydrophilic, while many organic pollutants are hydrophobic, which makes them less compatible and reduces the removal efficiency of such pollutants. In addition, oxide films are easily formed on the surface of zero-valent iron, which hinder the direct contact between active ingredients and target pollutants, thereby reducing the reactivity and efficiency of zero-valent iron.

[0004] These technical defects indicate that although zero-valent iron has broad application prospects in the field of environmental remediation, further research and technological improvements are still needed to improve its long-term stability, degradation efficiency and adaptability, so as to more effectively deal with complex contaminated sites and problems. Summary of the invention

[0005] The present invention provides an iron-nitrogen composite porous carbon microsphere material and a preparation method and application thereof. The iron-nitrogen composite carbon porous microsphere material provided by the present invention uses carbon as a matrix and its Fe 0 、Fe3N、FeC x , Fe3O4 is a composite component with a porous surface, and the zero-valent iron inside is less likely to oxidize, which can overcome the problem of rapid passivation of existing simple zero-valent iron microspheres during the repair process.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides an iron-nitrogen composite porous carbon microsphere material, comprising a porous carbon matrix and Fe0 、Fe3N、FeC x , Fe3O4, the Fe 0 As active electron donors, the Fe3N, FeC x and Fe3O4 are reduction active sites; wherein, based on the mass of the iron-nitrogen composite porous carbon microsphere material, Fe 0 The content is 25-33wt%.

[0008] The porous carbon matrix of the iron-nitrogen composite porous carbon microsphere material provided by the present invention has a porous structure, which can help adsorb pollutants. 0 As an active electron donor, it can directly react with chlorinated hydrocarbons (such as trichloroethylene) and promote the reductive dechlorination process of trichloroethylene by providing electrons, thereby converting trichloroethylene into less toxic compounds and ultimately into non-polluting methane, ethane, acetylene, ethylene, etc. x and Fe3O4 can serve as active centers, and the electron transfer properties of Fe3N and Fe3C and the catalytic properties of Fe3N can be used to accelerate the 0 The rate of transferring electrons to the target pollutant helps degrade trichloroethylene. Therefore, compared with a single zero-valent iron catalyst, the iron-nitrogen composite porous carbon microsphere material provided by the present invention can first adsorb trichloroethylene in water to quickly purify the water body in a very short time, and then perform a degradation reaction inside it and slowly release the degradation product.

[0009] Preferably, the iron-nitrogen composite porous carbon microsphere material structure is a hollow porous sphere with a pore diameter of 10 to 35 nm.

[0010] The present invention also provides a method for preparing an iron-nitrogen composite porous carbon microsphere material, comprising:

[0011] After S1, N,N-dimethylacetamide and triethylamine are mixed, 2-aminoterephthalic acid, sodium hydroxide and ferrous sulfate are added, and after mixing evenly, a precursor is obtained by hydrothermal reaction;

[0012] The precursors of S2 and S1 are dried and calcined in an inert atmosphere to obtain iron-nitrogen composite porous carbon microsphere materials.

[0013] The present invention uses N,N-dimethylacetamide, triethylamine, 2-aminoterephthalic acid, sodium hydroxide and ferrous sulfate to react under hydrothermal conditions; wherein ferrous sulfate is used as an iron ion source, 2-aminoterephthalic acid, triethylamine and N,N-dimethylacetamide are used as nitrogen ligands, and during the hydrothermal reaction, iron ions and nitrogen ligands are coordinated to form an intermediate of a coordination compound. The intermediate of the coordination compound is decomposed under high temperature conditions to produce an atomic iron-nitrogen coordination structure; part of the atomic iron-nitrogen coordination structure is reduced by CO generated by the decomposition of organic matter at high temperature and is called Fe 0; Excess organic ligands are also carbonized into a matrix due to high temperature.

[0014] Iron-nitrogen composite porous carbon microspheres are based on porous black carbon. 0 、Fe3N、FeC x , Fe3O4 are composite components, among which Fe 0 As electron donors, Fe3O4, FeCx and Fe3N are used to reduce active sites. x and Fe3N as semiconductor can accelerate Fe 0 The rate at which electrons are transferred to the target pollutants is increased, and the carbon matrix has good hydrophobicity and has a strong affinity for hydrophobic pollutants such as chlorinated hydrocarbons, thereby enhancing its performance in degrading pollutants. 0 The coating can effectively block Fe 0 The hydrogen evolution reaction with water weakens the water molecules to compete with pollutants for electrons, thereby increasing their electronic efficiency.

[0015] Preferably, in S1, the mass ratio of the N,N-dimethylacetamide, the triethylamine and the sodium hydroxide is (0.5-2):1:0.2.

[0016] Further preferably, in S1, the mass ratio of the N,N-dimethylacetamide, the triethylamine and the sodium hydroxide is (1-2):1:0.2.

[0017] Preferably, in S1, the mass ratio of the sum of the masses of the N,N-dimethylacetamide and the triethylamine to the mass of the ferrous sulfate is (10-50):1.

[0018] Further preferably, in S1, the mass ratio of the sum of the masses of the N,N-dimethylacetamide and the triethylamine to the mass of the ferrous sulfate is (10-30):1.

[0019] Further preferably, in S1, the mass ratio of the sum of the masses of the N,N-dimethylacetamide and the triethylamine to the mass of the ferrous sulfate is (20-30):1.

[0020] Preferably, in S1, the mass ratio of the 2-aminoterephthalic acid to the ferrous sulfate is 1:1.

[0021] Too low a dosage of ferrous sulfate or too low a reaction temperature will result in the Fe 0 The content is too low; too low dosage of N,N-dimethylacetamide and triethylamine will lead to insufficient iron-nitrogen coordination and failure to form effective Fe3N active sites.

[0022] Preferably, in S1, the sodium hydroxide is added in the form of 40-70 g / L sodium hydroxide solution.

[0023] Further preferably, the concentration of the sodium hydroxide solution is 50-60 g / L.

[0024] Preferably, in S1, the temperature of the hydrothermal reaction is 190-210° C., and the time of the hydrothermal reaction is 10-12 h.

[0025] Further preferably, in S1, the temperature of the hydrothermal reaction is 200° C., and the time of the hydrothermal reaction is 12 h.

[0026] Preferably, in S2, the inert atmosphere is nitrogen and / or argon.

[0027] Preferably, in S2, the calcination temperature is 500-800°C, the calcination heating rate is 8-10°C / min, and the calcination time is 1-4h.

[0028] A calcination time that is too long or a heating rate that is too fast will result in a low material yield and insufficient effective ingredients.

[0029] Further preferably, in S2, the calcination temperature is 700°C, the calcination heating rate is 10°C / min, and the calcination time is 2h.

[0030] Under these conditions, the Fe 0 It has the highest content, uniform pore structure, and stable Fe3N coordination structure, and has better removal effect on chlorinated hydrocarbon organic pollutants.

[0031] The present invention also provides the use of the iron-nitrogen composite porous carbon microsphere material or the iron-nitrogen composite porous carbon microsphere material prepared by the above preparation method in in-situ remediation of groundwater containing chlorinated hydrocarbon organic pollutants.

[0032] Preferably, the chlorinated hydrocarbon organic pollutants are one or more of 1,2-dichloroethane, vinyl chloride, 1,1-dichloroethylene, trans-1,2-dichloroethylene, cis-1,2-dichloroethylene, trichloroethylene, tetrachloroethylene, tetrachloroethane, methyl chloride, dichloromethane, chloroform, carbon tetrachloride, hexachlorobutadiene, trichloropropane and chloroform.

[0033] Preferably, the application method is: adding the iron-nitrogen composite carbon porous microsphere material into groundwater containing chlorinated hydrocarbon organic pollutants to adsorb and degrade the chlorinated hydrocarbon organic pollutants in the groundwater.

[0034] Preferably, the usage ratio of the iron-nitrogen composite carbon porous microsphere material to the chlorinated hydrocarbon organic pollutant is (1-3) g:1 mL.

[0035] Therefore, the present invention has the following beneficial effects:

[0036] (1) The iron-nitrogen composite carbon porous microsphere material provided by the present invention is based on carbon and its Fe 0 、Fe3N、FeC x , Fe3O4 is a composite component with a porous surface, and the zero-valent iron inside is less likely to oxidize, which can overcome the problem of rapid passivation of existing simple zero-valent iron microspheres during the repair process.

[0037] (2) The present invention controls the raw material ratio, hydrothermal reaction temperature and time, calcination temperature and time, and heating rate during the synthesis process to adjust the Fe content of the Fe-N composite carbon porous microsphere material. 0 The content is maintained at 25-30wt%, ensuring the overall reaction activity of the iron-nitrogen composite carbon porous microsphere material.

[0038] (3) The method of the present invention is easy to operate, has a short preparation cycle, and has a high removal efficiency for chlorine-containing organic pollutants, and reduces and converts them into pollution-free methane, ethane, acetylene, ethylene, etc., which is very suitable for the in-situ remediation process of groundwater. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a scanning electron microscope image of the iron-nitrogen composite carbon porous microsphere material prepared in Example 1.

[0040] Figure 2 This is the XRD spectrum of the iron-nitrogen composite carbon porous microsphere material prepared in Example 1.

[0041] Figure 3 This is the pore size distribution diagram of the iron-nitrogen composite carbon porous microsphere material prepared in Example 1. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0043] [Example]

[0044] Example 1

[0045] (1) Add 1 g of ferrous sulfate, 10 g of N,N-dimethylacetamide (DMA), 10 g of triethylamine, 1 g of 2-aminoterephthalic acid (2-APDC), and 4 mL of 50 g / L sodium hydroxide solution to a 50 mL hydrothermal reactor. After mixing evenly, seal the reactor and react at 200 °C for 12 h. After cooling to room temperature, separate the product. Wash the product three times with N,N-dimethylacetamide and then with deionized water three times. After filtering, freeze-dry the product to obtain the precursor.

[0046] (2) The precursor of (1) is placed in a tubular furnace, heated to 700°C at 10°C / min and calcined for 2 h in a nitrogen atmosphere. After calcination, the precursor is cooled to room temperature and taken out to obtain an iron-nitrogen composite carbon porous microsphere material.

[0047] The iron-nitrogen composite porous carbon microsphere material prepared in this embodiment was characterized and tested, and the results are as follows: Figure 1 , 2 , as shown in 3; Figure 1 This is a scanning electron microscope image of the iron-nitrogen composite porous carbon microspheres prepared in Example 1. The results show that the iron-nitrogen composite porous carbon microspheres synthesized in this example are porous, hollow and porous; Figure 2 The XRD spectrum shows that the iron-nitrogen composite porous carbon microsphere material synthesized in this embodiment contains Fe 0 , Fe3N, Fe3C, Fe3O4; Figure 3 The pore size distribution diagram shows that the pore size of the iron-nitrogen composite porous carbon microsphere material synthesized in this embodiment is mainly 10-35 nm. 0 The mass percentage is 30%.

[0048] Referring to the complete scheme given in Example 1, the experiments of Examples 1 to 12 and Comparative Examples 1 to 5 were carried out according to the reaction conditions in Table 1. Except for the changes in the reaction condition parameters in Table 1 below, the rest of the scheme content is exactly the same as that of Example 1. Table 2 shows the relationship between the substances in each Example / Comparative Example at the specific dosage in Table 1.

[0049] Table 1 Reaction conditions

[0050]

[0051]

[0052] Table 2 Relationship between substances under different reaction conditions in Table 1

[0053]

[0054]

[0055]

Performance test

[0056] Select trichloroethylene, trichloromethane, dichloromethane, tetrachloroethylene, trichloropropane, cis-1,2-ethylene as target pollutants, and evaluate the reactivity and efficiency of iron-nitrogen composite porous carbon microspheres obtained in Examples 1 to 12 and Comparative Examples 1 to 5. The specific details are as follows: 26 mg of iron-nitrogen composite porous carbon material (prepared by any of the schemes in Examples 1 to 12 and Comparative Examples 1 to 5) was added to a reaction bottle with a volume of 52 mL, and then 26 mL of deoxygenated water (pure water was stripped with nitrogen for 30 min), that is: the mass concentration of the iron-nitrogen composite porous carbon microspheres was 1 g / L, sealed with a lid with a polytetrafluoroethylene liner, and then 15 μL of trichloroethylene solution (17.9 mg / L) was added with a microinjector, that is, the initial concentration of trichloroethylene was set to 10 ppm, and the residual concentration of trichloroethylene in the reaction system was monitored by gas chromatography tracking. The results are recorded in Table 3.

[0057] The results in Table 3 show that the iron-nitrogen composite porous carbon materials obtained in Examples 1 to 4 can achieve a removal rate of trichloroethylene close to 100% after 15 minutes of reaction. The reaction products of the iron-nitrogen composite porous carbon materials obtained in Example 1 were analyzed and determined, and it was found that the reaction products were ethylene, acetylene and ethane, as well as a small amount of C3-C6 hydrocarbon compounds. The carbon equivalent of the reaction product accounted for 10% of the carbon equivalent of the initial trichloroethylene, and the carbon equivalent of the reaction product accounted for 68% of the carbon equivalent of the initial trichloroethylene after 24 hours. The carbon equivalent of the reaction product accounted for 89% of the carbon equivalent of the initial trichloroethylene after 48 hours. The concentration of trichloroethylene was never detected after 15 minutes. This result shows that the iron-nitrogen composite porous carbon material obtained in Example 1 first adsorbs trichloroethylene in water and then degrades it, and the reaction product is slowly released.

[0058] The iron-nitrogen composite porous carbon material prepared in Example 1 has a good adsorption and degradation effect on various pollutants such as trichloroethylene, trichloromethane, dichloromethane, tetrachloroethylene, trichloropropane, cis-1,2-ethylene, etc. After reacting for 15 minutes, the adsorption removal rate can be maintained at more than 90%.

[0059] Table 3 Adsorption and degradation effects of different iron-nitrogen composite carbon porous microsphere materials on different pollutants

[0060]

[0061]

Claims

1. An iron-nitrogen composite porous carbon microsphere material, characterized in that: The porous carbon matrix and the Fe 0 、Fe3N、FeC x , Fe3O4, the Fe 0 As active electron donors, the Fe3N, FeC x and Fe3O4 are reduction active sites; wherein, based on the mass of the iron-nitrogen composite porous carbon microsphere material, Fe 0 The content is 25-33wt%.

2. The iron-nitrogen composite porous carbon microsphere material according to claim 1, characterized in that: The iron-nitrogen composite porous carbon microsphere material structure is a hollow porous sphere with a pore diameter of 10 to 35 nm.

3. The method for preparing the iron-nitrogen composite porous carbon microsphere material according to claim 1 or 2, characterized in that: include: After S1, N,N-dimethylacetamide and triethylamine are mixed, 2-aminoterephthalic acid, sodium hydroxide and ferrous sulfate are added, and after mixing evenly, a precursor is obtained by hydrothermal reaction; The precursors of S2 and S1 are dried and calcined in an inert atmosphere to obtain iron-nitrogen composite porous carbon microsphere materials.

4. The preparation method according to claim 3, characterized in that: In S1, the mass ratio of the N,N-dimethylacetamide, the triethylamine and the sodium hydroxide is (0.5-2):1:0.

2.

5. The preparation method according to claim 3, characterized in that: In S1, the mass ratio of the sum of the masses of the N,N-dimethylacetamide and the triethylamine to the mass of the ferrous sulfate is (10-50):

1.

6. The preparation method according to claim 3, 4 or 5, characterized in that: In S1, the sodium hydroxide is added in the form of 40-70 g / L sodium hydroxide solution.

7. The preparation method according to claim 3, 4 or 5, characterized in that: In S1, the temperature of the hydrothermal reaction is 190-210° C., and the time of the hydrothermal reaction is 10-12 hours.

8. The preparation method according to claim 3, characterized in that: In the S2, the calcination temperature is 500-800°C, the calcination heating rate is 8-10°C / min, and the calcination time is 1-4h.

9. Use of the iron-nitrogen composite porous carbon microsphere material as claimed in any one of claims 1 to 2 or the iron-nitrogen composite porous carbon microsphere material prepared by the preparation method as claimed in any one of claims 3 to 8 in in-situ remediation of groundwater containing chlorinated hydrocarbon organic pollutants.

10. The use according to claim 9, characterized in that The chlorinated hydrocarbon organic pollutants are one or more of 1,2-dichloroethane, vinyl chloride, 1,1-dichloroethylene, trans-1,2-dichloroethylene, cis-1,2-dichloroethylene, trichloroethylene, tetrachloroethylene, tetrachloroethane, methyl chloride, dichloromethane, chloroform, carbon tetrachloride, hexachlorobutadiene, trichloropropane and chloroform.